Analysis of the Implementation of the Regulation of the Minister of Home Affairs Number 4 of 2010 concerning Guidelines for Integrated Sub-district Administrative Services in South Central Timor Regency - Ardi Aprianus Benu; Susanti Susanti; Pardamaean Dauly (Jurnal Indonesia Sosial Teknologi, 2024)
Since the Reformasi era in Indonesia, there has been a significant shift from a centralistic-autocratic government to democratization and decentralization, with the aim of improving the quality of public services. This research specifically evaluates the implementation of Permendagri No. 4 of 2010 in South Central Timor Regency (TTS), focusing on the implementation of the Integrated Sub-district Administrative Services Program (PATEN). A qualitative approach is used, involving descriptive methods to analyze the phenomenon of PATEN policy implementation. Data collection includes interviews, observations, literature reviews, and documentation, analyzed through the Van Meter and Van Horn (1975) policy implementation model. The findings reveal that not all sub-districts in Indonesia, including those in TTS Regency, have implemented the PATEN program. Key barriers include limited funding, human resources, and the handover of authority to sub-districts. Although the delegation of authority by Regent Regulation No. 22 of 2014 has increased sub-district responsibilities, significant challenges remain in executing licensing functions. This research highlights the need for stronger regulatory frameworks, enhanced resources, and stakeholder collaboration to achieve the intended goals of the PATEN program.